Effect of Reynolds Number on Minor Loss Coefficient of a T-Strainer - Mohamad Din, Hamzah Fansuri; Idris, Ahmad Fu'ad; Azlan, Mohd Azwir (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Loss coefficient is very important to determine minor loss occur in the piping system. This project is carried out because there is no information for the T-strainer loss coefficient. So, this project is done to determine the value of loss coefficient for T-strainer. To determine T-strainer loss coefficient at different Reynolds number, the apparatus needs to be design and fabricated. The result shows that at low Reynolds number (Re < 20000), minor loss coefficient value is inversely proportional to the value of Reynolds number while at high Reynolds number (Re > 25000), the value of minor loss coefficient almost constant. To determine the optimal link between the Reynolds number and the value of the minor loss coefficient at low Reynolds number, the correlation and regression methods were used. The outcome demonstrates that the best correlation between the Reynolds number and the value of the minor loss coefficient was found is the cubic equation. However, the quadratic relationship graph pattern is more preferable than the cubic relationship graph pattern. The value of R and R-squared are 0.9902, 0.9804 respectively. At high Reynolds number, the loss coefficient for T-strainer is 13.37.